Using WEB Services in SCADA Applications. (2015) - Turc, Traian
Abstract: In order to access databases without have direct access, WEB Services can offer an easy way to benefits on data from databases. SCADA systems are built often around of databases. In such of case using WEB services is better solutions in order to avoid sophisticated way to access directly databases.